Constitutional Rights Protection of Voters as Vulnerable Groups in Local Election Disputes: A Comparative Perspective on Indonesia, Brazil, and South Korea - Biku Bajenggo; Adene Pertamo; Carlos Eduardo Diaz Souza (RechtIdee, 2026)
Study Objective: To examine the limits of the District Court's jurisdiction in adjudicating election crimes by referring to the Constitutional Court Decision No. 313/PHPU.BUP-XXIII/2025 and Muara Teweh District Court Decision No. 39/Pid.Sus/2025/PN.Mtw arising from the local election dispute in North Barito Regency.Method/Approach: This study is normative, employing a comparative analysis of Indonesia, Brazil, and South Korea and applying statute, conceptual, and case-based approaches.Novelty: This study is novel in that it places the restoration of voters’ constitutional rights at the core objective of Indonesia’s electoral justice system.Findings: The District Court's absolute jurisdiction is strictly limited to determining the criminal responsibility of individual perpetrators and does not extend to administrative sanctions, such as disqualifying candidate pairs. Second, the Constitutional Court has exclusive authority to adjudicate disputes over election results and may consider decisions of criminal courts as corroborating evidence when protecting voters' constitutional rights. Third, effective protection of voters as a vulnerable group, particularly those whose rights are directly affected by money politics, vote manipulation, and limited legal standing in disputes over election results, demands a clear division of institutional jurisdiction to prevent normative voids that could undermine democratic legitimacy.Conclusion: This article argues that strengthening the electoral justice system requires explicit legislative synchronization between the two jurisdictional regimes to ensure a meaningful restoration of voters' constitutional rights.